Location and educational signals - Raoul van Maarseveen (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2025)
Place shapes the educational attainment of children, yet the underlying reasons remain poorly understood. In this paper, I investigate the role of spatial differences in educational signals received by students. Using Dutch administrative data combined with high-stakes national exam scores, I show that students receive less ambitious track recommendations in rural areas conditional on ability. The spatial difference is comparable to the impact of having a university-educated parent and explains around half of the spa- tial difference in academic track enrollment. Key mechanisms are spillovers from high SES peers and stronger beliefs in the importance of education among urban teachers.
Keywords: 330; Spatial Inequality; Educational attainment; Teacher Bias; Human Capital